PERAN PEMBIMBING KEMASYARAKATAN DALAM MENANGANI ANAK BERHADAPAN DENGAN HUKUM DI MASA PANDEMI COVID-19 - Frengky Hartono; Mitro Subroto (P3M STISIPOL Dharma Wacana Metro, 2022)
Community advisors are correctional officers who have been appointed and appointed as community advisors and can be dismissed by the minister in accordance with the regulations that govern them. The main tasks of community supervisors are mentoring, community research (litmas), mentoring and coaching, and supervision. This study aims to determine the implementation of the duties and functions of community mentors during the COVID-19 pandemic at the Class II Penitentiary Kediri. The method used in this research is qualitative-descriptive in which the research explains in detail and depth about the phenomena that occur. Data collection was done by means of literature review, observation and interviews. Based on the results of the study, it was shown that the implementation of the duties and functions of community supervisors was not running effectively and efficiently. During the COVID-19 pandemic, there were several regulations that did not allow the implementation of tasks and functions to run optimally. It is shown by the government's ban on gatherings to prevent the transmission of the covid-19 virus, so all activities run virtual through zoom meetings and video calls, related to tasks and functions that require face-to-face meetings, cannot be carried out optimally such as self-help guidance.